Upaya Pemenuhan Kesejahteraan Lansia melalui Pendekatan Biopsikososial di Panti Wredha Siti Khadijah Kota Cirebon - Tisfah, Mutia; Suryadi, Suryadi; Handayani, Amelia Dwi (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2025)
The growth of the elderly population in Indonesia is increasing every year and there is a risk of several health problems including physical, mental, social problems and the occurrence of several other diseases. The increasing health problems affect the quality of life of the elderly. Therefore, it is important to have a place for the elderly, one of which is the Siti Khadijah Nursing Home in Cirebon City which contributes to the welfare of the elderly through various activities to increase the independence and welfare of the elderly. The Biopsychosocial approach is an effort to improve the welfare of the elderly. Thus, this study aims to identify the initiatives carried out by the Siti Khadijah Nursing Home in Cirebon City to fulfill the welfare of the elderly through the Biopsychosocial approach. This type of research uses a qualitative method with descriptive analysis. From the results of the study, it can be concluded that the Role of the Siti Khadijah Nursing Home has a positive impact on the quality of life of the elderly in fulfilling the welfare of the elderly, especially in the field of health services. This institution is able to meet physical, psychological, social and environmental needs. However, it cannot be said to be successful overall in providing perfect welfare because there are factors that influence the Biopsychosocial approach.